Non-destructive diagnosis by colorimetry of building stone subjected to high temperatures. Issue 6 (2nd July 2016) - Beck, Kevin; Janvier-Badosa, Sarah; Brunetaud, Xavier; Török, Ákos; Al-Mukhtar, Muzahim
Abstract : When a building is exposed to fire, the building materials are subjected to high temperatures which cause changes in their structural and aesthetic properties. As the replacement of degraded stones is expensive, a diagnosis of degradation by using non-destructive tests could help to select the appropriate restoration method. The objective of this study is to propose an in situ methodology to assess the state of degradation of stone after exposure to fire by providing a relationship between the state of damage of the stone and its colorimetric properties. Laboratory tests were performed on tuffeau limestone, heated at different temperatures, from 100 to 900 °C. Colorimetric measurements were compared to another non-destructive test, ultrasonic P-wave velocity measurements, which are widely used for damage diagnosis of concrete structures.